NILAI KONVERSI UJI KUAT TEKAN VARIASI BENTUK PAVING BLOCK TERHADAP BENTUK SAMPEL UJI SNI 03-0691-1996 - Barkiah, Ida; Yasin, Muhammad (Jurnal Teknologi Berkelanjutan, 2020)
This study aims to determine the compressive strength conversion factor of various paving blocks shape to the standard test shape of paving blocks (SNI 03-0691-1996). The manufacture of paving blocks samples uses a ratio of 1:2:0.2 for cement, fine aggregate, and coarse aggregate. This study used a mixture of 15% fly ash as a partial replacement of cement. The shape of paving blocks were rectangular measuring 21x10.5x8 cm, hexagon with a side size of 11.5 cm and a thickness of 6 cm, and a bishop's hat measuring 30x21x8 cm. As for paving block specimens with standard shapes measuring 6x6x6 cm cubes for hexagons, and 8x8x8 cm cubes for rectangular shapes and bishop's hats. The compressive strength and water absorption of paving blocks were tested at the age of 28 days. In this study, the results of the compressive strength testing of paving blocks with standard shapes were higher than the compressive strength values of rectangular, hexagon, and bishop's hats. The amount of conversion factor obtained on paving blocks with 15% fly ash are 1.06, 1.32, and 1.13 for rectangular, hexagons, and bishop’s hats respectively. In addition, the average water absorption obtained on paving blocks with 15% fly ash are 2.92%, 2.79%, and 2.96% for rectangular, hexagons, and bishop’s hats respectively.